Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Select the correct answer.

Select the simplification that accurately explains the following statement.
[tex]\[ \sqrt[4]{2}=2^{\frac{1}{4}} \][/tex]

A. [tex]\(\left(2^{\frac{1}{4}}\right)^4=2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}}=2^{\frac{1}{4}+\frac{1}{4}+\frac{1}{4}+\frac{1}{4}}=2^{\frac{4}{4}}=2^1=2\)[/tex]

B. [tex]\(\left(2^{\frac{1}{4}}\right)^4=2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}}=2 \cdot\left(\frac{1}{4}+\frac{1}{4}+\frac{1}{4}+\frac{1}{4}\right)=2 \cdot \frac{4}{4}=2\)[/tex]

C. [tex]\(\left(2^{\frac{1}{4}}\right)^4=2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}}=2^{\frac{1}{4} \cdot \frac{1}{4} \cdot \frac{1}{4} \cdot \frac{1}{4}}=2^{\frac{4}{4}}=2^1=2\)[/tex]

D. [tex]\(\left(2^{\frac{1}{4}}\right)^4=2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}}=4 \cdot 2^{\frac{1}{4}}=4 \cdot \frac{1}{4} \cdot 2=2\)[/tex]


Sagot :

To solve the given problem, we need to follow the steps of simplification for the expression [tex]\(\left(2^{\frac{1}{4}}\right)^4\)[/tex].

Let's evaluate this step by step:

1. [tex]\(\left(2^{\frac{1}{4}}\right)^4\)[/tex].

2. When raising a power to another power, the exponents get multiplied:
[tex]\[ \left(a^{m}\right)^{n} = a^{m \cdot n} \][/tex]
Applying this property, we get:
[tex]\[ \left(2^{\frac{1}{4}}\right)^{4} = 2^{\frac{1}{4} \cdot 4} \][/tex]

3. Simplifying the exponent:
[tex]\[ 2^{\frac{1}{4} \cdot 4} = 2^{1} \][/tex]

4. Any number to the power of 1 is the number itself:
[tex]\[ 2^{1} = 2 \][/tex]

Therefore, the correct simplification according to the rules of exponents is [tex]\(2\)[/tex].

Checking the provided options:

A. [tex]\(\left(2^{\frac{1}{4}}\right)^4=2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}}=2^{\frac{1}{4}+\frac{1}{4}+\frac{1}{4}+\frac{1}{4}}=2^{\frac{4}{4}}=2^1=2\)[/tex]

This is accurately done, so this is correct.

B. Using addition inside the base of 2, that leads to confusion and is incorrect.

C. Product of fractions rather than summation is applied incorrectly and is incorrect.

D. Incorrectly uses direct multiplication without correct exponent rules, is also incorrect.

The accurate simplification is given by option A. Therefore, the correct answer is:
[tex]\[ \boxed{A} \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.